2019
DOI: 10.1001/jamanetworkopen.2019.7584
|View full text |Cite
|
Sign up to set email alerts
|

Association of an Emergency Department–Based Intensive Care Unit With Survival and Inpatient Intensive Care Unit Admissions

Abstract: This cohort study compares 30-day mortality and inpatient intensive care unit (ICU) admissions before and after the implementation of a novel emergency department–based ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 24 publications
2
99
0
Order By: Relevance
“…ICU admissions from the ED fell by 12.9%, and short‐stay ICU admissions (ICU length of stay < 24 hr) were 37.1% lower. Time to ICU‐level care was reduced by 1.9 hours, and more patients received ICU‐level care within 6 hours (77.6% vs 58.3%) 64 . Similar comparative data have not been published in other RCU models, but the role of the RCU will be clarified through more detailed studies in other practice settings.…”
Section: Resultsmentioning
confidence: 56%
“…ICU admissions from the ED fell by 12.9%, and short‐stay ICU admissions (ICU length of stay < 24 hr) were 37.1% lower. Time to ICU‐level care was reduced by 1.9 hours, and more patients received ICU‐level care within 6 hours (77.6% vs 58.3%) 64 . Similar comparative data have not been published in other RCU models, but the role of the RCU will be clarified through more detailed studies in other practice settings.…”
Section: Resultsmentioning
confidence: 56%
“…Structural changes for critical care in the ED, such as the CCSU described in this manuscript, have been reported infrequently, although none involve step‐down critical care provided by advanced practice providers. The University of Michigan Medical Center opened a 9‐bed intensive care unit adjacent to its adult ED in 2015 with a medical staff consisting of emergency medicine physicians and residents, critical care fellows and physician assistants 10 . Study authors reported a decrease in risk‐adjusted 30‐day mortality among all ED patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 These alternative care models, while highly variable in structure, provide more specialized opportunities for the critical care medicine-trained EP and support for both the EM and ICU inpatient teams and potentially improved outcomes for critically ill ED boarding patients. 12…”
Section: Discussionmentioning
confidence: 99%